Whether Plasma Endocrine And Biochemical Profile Can Predict Early Pregnancy In Mares - Rabari, M.l.; Shah, R.G.; Tank, P.H.; Dhami , A.J. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
This work was carried out on 32 mares selected randomly from different areas of Saurastra region of Gujarat state during March-August, 2011. The mares bred naturally were subjected to per rectal examinations between day 20 and 150 post-breeding together with periodic blood sampling and were divided into pregnant (22) and non-pregnant (10) groups. The pregnant mares were further distributed in three stages as per the gestation days, viz., i) Stage-I: 0-35 days of gestation (4), ii) Stage-II: 36-75 days of gestation (7), iii) Stage-III: 76-150 days of gestation (11). The mean plasma progesterone level (ng/ml) of pregnant mares was significantly higher in stage-III (20.34 ± 2.13) followed by stage-I (15.55 ± 3.54) and II (13.51 ± 1.81), whereas in non-pregnant mares significantly lower mean P4 level (0.97 ± 0.15) was observed. The mean plasma estradiol-17β concentration (pg/ml) was significantly higher (P< 0.05) in pregnant mares of stage-III (289.82 ± 73.05) than those in stage-I (28.50 ± 4.52) and II (43.14 ± 11.90), and even in non-pregnant ones (23.80 ± 1.82). The mean plasma total cholesterol level was significantly (P126 pg/ml) and progesterone (> 8.2 ng/ml) during 76- 150 days post-breeding can be used as diagnostic marker for early pregnancy in mares.
Keywords: Mare; Early pregnancy; Farmer’s door; Hormonal profile; Biochemical profile